Compression of self-ion implanted iron micropillars - Grieveson, E; Armstrong, D; Xu, S; Roberts, S (Elsevier, 2012)
Ion implantation causes displacement damage in materials, leading to the formation of small dislocation loops and can cause changes to the material's mechanical properties. Samples of pure Fe were subjected to Fe + implantation at 275°C, producing damage of ∼6 dpa to ∼1 μm depth. Nanoindentation into implanted material shows an increase in hardness compared to unimplanted material. Micropillars were manufactured in cross-section specimens of implanted and unimplanted material and compressed using a nanoindenter. The implanted pillars have a deformation mode which differs markedly from the unimplanted pillars but show no change in yield-stress. This suggests that the controlling mechanism for deformation is different between nanoindentation and micropillar compression and that care is needed if using micropillar compression to extract bulk properties of irradiated materials. © 2012 Elsevier B.V. All rights reserved.